2017
DOI: 10.1093/ofid/ofx243
|View full text |Cite
|
Sign up to set email alerts
|

Extended Screening Costs Associated With Selecting Donors for Fecal Microbiota Transplantation for Treatment of Metabolic Syndrome-Associated Diseases

Abstract: BackgroundKnowledge of the impact of the gut microbiome on conditions other than Clostridium difficile infection has been rapidly increasing, and the potential usefulness of fecal microbiota transplantation (FMT) in these indications is being explored. The need to exclude donors with an increased risk of these diseases has left uncertainties regarding the cost and feasibility of donor screening. The aim of this study was to compare our experience to other donor-screening programs and report the costs associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…Observational data from a large stool bank suggest a high-rate of drop out and health-related exclusion from initial contact to stool donor qualification 42. Others small academic stool banks from Australia, Canada, USA and Denmark have reported similar challenges in procuring healthy donors 28 44–47. Accordingly, we recommend dedicated donor operational personnel who use a structured workflow to ensure access to material.…”
Section: Resultsmentioning
confidence: 89%
“…Observational data from a large stool bank suggest a high-rate of drop out and health-related exclusion from initial contact to stool donor qualification 42. Others small academic stool banks from Australia, Canada, USA and Denmark have reported similar challenges in procuring healthy donors 28 44–47. Accordingly, we recommend dedicated donor operational personnel who use a structured workflow to ensure access to material.…”
Section: Resultsmentioning
confidence: 89%
“…The parasites Dientamoeba fragilis and Blastocystis hominis in stools have been linked to gastrointestinal symptoms and their presence has been a common cause of donor exclusion in FMT studies 74. The pathogenicity of these organisms, however, has never been established in humans, and some studies suggest they may in fact be associated with health 75–83.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to this guidance, one review published in 2017 suggested screening for ESBL, but several others did not. [21][22][23] Owing to discrepancies in recommendations, clinical trials had not adopted ESBL as a standard screening metric for donor exclusion criteria, nor had many stool banks. [24][25][26] The guidance provided was a step in the right direction.…”
Section: Donor Screeningmentioning
confidence: 99%
“…30 However, this timeline is rarely supported by evidence and varies widely in the literature from 3 to 6 months, even though research shows that antimicrobial exposure can have impacts lasting longer than 6 months. 22,26,31,32 Age has also been indicated as an important factor to consider. A suggested age range for donors is often between 18 and 50 years old.…”
Section: Donor Screeningmentioning
confidence: 99%